2018
DOI: 10.3390/publications6030036
|View full text |Cite
|
Sign up to set email alerts
|

A Bridge between Society and Universities: A Documentary Analysis of Science Shops

Abstract: Citizen science surfaced as a new way of conducting research and science shops are one of the initiatives in which citizen collaboration with scientists has been most visible. These organisations provide independent and participatory support for research in response to civil society's problems/needs. Although science shops have pioneered the furthering of citizen participation, the general public is still scantly aware of their existence. This study aimed to explore that matter, identifying and analysing the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A key theme that emerged in many articles is the lack of visibility that Science Shops face. Despite being pioneers in incorporating citizen participation, it seems that the general public is still unaware of their existence [De Filippo et al, 2018]: Science Shops have struggled to create visibility [Dorland, Clausen and Søgaard Jørgensen, 2019]. This is pinpointed as a major obstacle to the recognition of their work [Fischer, Leydesdorff and Schophaus, 2004;Schlierf and Meyer, 2013] and, here, performing impact evaluations and communicating their findings are crucial to ensuring their achievements gain the recognition they deserve.…”
Section: Impact Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…A key theme that emerged in many articles is the lack of visibility that Science Shops face. Despite being pioneers in incorporating citizen participation, it seems that the general public is still unaware of their existence [De Filippo et al, 2018]: Science Shops have struggled to create visibility [Dorland, Clausen and Søgaard Jørgensen, 2019]. This is pinpointed as a major obstacle to the recognition of their work [Fischer, Leydesdorff and Schophaus, 2004;Schlierf and Meyer, 2013] and, here, performing impact evaluations and communicating their findings are crucial to ensuring their achievements gain the recognition they deserve.…”
Section: Impact Evaluationmentioning
confidence: 99%
“…Publications. To date, the scientific production of Science Shops has tended to be very meagre [De Filippo et al, 2018], their resources being principally available in 'grey literature', primarily in the form of Master's theses and CSO reports [Vargiu, Cocco and Ghibellini, 2019]. This situation is doubtless attributable to the lack of time and resources available to Science Shop staff [De Filippo et al, 2018] who are obliged to focus mostly on their primary research goal rather than on communicating and publishing their results.…”
Section: Impact Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal access to the scientific literature has to be 'illegally' provided by a grassroots movement on the backs of a suicide and a forced exile, 3 while some major scientific professional associations are still actively fighting against it. 4 Community-engaging institutional initiatives have seen an expansion 5 (De Filippo et al, 2018) under recent trends towards Responsible Research and Innovation (RRI; Robinson et al, 2020), but they will remain a distant reality for most science if they are not radically scaled-up. At the same time, both private and public universities in many countries have raised costs for diplomas whose value has entered a regime of diminishing returns.…”
Section: Résumémentioning
confidence: 99%
“…This European project involves 18 public and private organizations from different EU countries working together to create a new research method, based on a "bottom-up" approach, where private citizens and civil society organizations are actively involved in the research process. A survey conducted by this project revealed that the awareness of science shops among actors is relatively low and that the public is still poorly aware of their existence (De Filippo et al 2018). WatShop, 4 the new science shop set up at the end of 2018 at the University of Brescia (Lombardy, northern Italy), was developed in this framework and started its activities at the beginning of 2019.…”
Section: Issnet -Improving Science Shop Networking Interacts -Improving Interaction Between Ngos Universities and Science Shops Scipas -Smentioning
confidence: 99%